PENGARUH KONSELING MULTIKULTURAL DALAM MENINGKATKAN KOMUNIKASI INTERPERSONAL MAHASISWA JURUSAN BIMBINGAN DAN KONSELING FKIP UNIVERSITAS BORNEO TARAKAN - Nazwa Manurung; Siti Rahmi (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2022)
The purpose of this research is to improve interpersonal communication of Guidance and Counseling Department students through multicultural counseling. To be a good BK teacher, you must have good interpersonal communication as well. This study uses quantitative and qualitative methods using interpersonal communication questionnaires and interview techniques as data collection tools. The results showed that of the 12 BK students who were used as research subjects, there were still some people who lacked interpersonal communication. It was found that some subjects still use their personal values of a tribe when communicating with other people from that tribe, so that interpersonal communication will not be objective. Objective interpersonal communication skills are very much needed as BK teachers later, so students must learn to view other people objectively and place values on that person's ethnicity first. Multicultural counseling conducted on the subject has an impact on his interpersonal skills. Subjects whose interpersonal communication was lacking at the end of the study showed an increase based on the interpersonal communication questionnaire